Overview of hydrogen production technologies for fuel cell utilization - Rahim Malik, Fawad; Yuan, Hai-Bo; Moran, James C.; Tippayawong, Nakorn (Engineering science and technology, an international journal, 2023)
With rapidly depleting fossil fuels and growing environmental alarms due to their usage, hydrogen as an energy vector provides a clean and sustainable solution. However, the challenge lies in replacing mature fossil fuel technology with efficient and economical hydrogen production. This paper provides a techno-economic, and environmental overview of H2 production technologies. Reforming of fossil fuels is still considered as the backbone of large-scale H2 production. Whereas renewable hydrogen has technically advanced and improved, its cost remains an area of concern. Finding alternative catalytic materials would reduce such costs for renewable hydrogen production. Taking a mid-term timeframe, a viable scenario is replacing fossil fuels with solar hydrogen production integrated with water splitting methods, or from biomass gasification. Gasification of biomass is the preferred option as it is carbon neutral and cost-effective, producing hydrogen at 1.77 – 2.77 $/kg of H2. Among other uses of hydrogen in industrial applications, the most viable approach is to use it in hydrogen fuel cells for generating electricity. Commercialization of fuel cell technology is hindered by a lack of hydrogen infrastructure. Fuel cells and hydrogen production units should be integrated to achieve desired results. Case studies of different fuel cells and hydrogen production technologies are presented at the end of this paper, depicting a viable and environmentally acceptable approach compared with fossil fuels.